Ethnicity, voting and the promises of the independence movement in Mwanza, Tanzania - Malipula, Mrisho Mbegu (Afrika Focus, 2017)
This report explores influences of ethnicity on determining voters’ choices in Tanzania. It questions the dominant neo-patrimonial and hybrid approaches to African politics, which argue that primordial (traditional) ways of organising politics inform ethnic voting. This study deviates from ethnic structure theorists arguing that outcomes of elections are determined by the ability of ethnic groups to form minimum winning coalitions (MWCs). Instead, it looks at the ideational structure of nationalisation, driven mainly by the promises of the independence movement (PsIM). The movement created an experiential and discursive framework that emphasises depoliticisation of ethnicity, peacefulness and national unity as ‘Tanzanian’ national values. The frame is intact despite Tanzania’s ethnic diversity and liberal socio-economic as well as political reforms it has undergone overtime. The report critically divulges this capacity to build a political organisation encompassing the political leaders, ideals of the independence movement and the people in informing voters’ choices. Key words: ethnicity, neo-patrimonialism, hybrid regimes, promises of independence and voting